CRIMINAL LIABILITY FOR PUBLIC INCITEMENT TO COMMIT ILLEGAL ACTS - Treļs, Ēriks (Administrative and Criminal Justice, 2016)
On 18 March 2016 President of Latvia Raimonds Vējonis posted a letter to the Legal Affairs Committee of the Parliament of the Republic of Latvia (Saeima) regarding the amendments to the Criminal Law (Nr.514/Lp12). President of Latvia drew attention of the Saeima to several controversial definitions of the amendments to the law requiring a clearer and more precise wording so that the proposed statutory solutions would not contradict the Constitution of Latvia (Satversme) and international commitments of Latvia. The article aims to initiate a debate on problems related to the application of the Section 81 of the Criminal Law. The author offers his vision of the regulatory framework application problems.